Clinical impact and risk stratification of balloon angioplasty for femoropopliteal disease in nitinol stenting era: Retrospective multicenter study using propensity score matching analysis. (14th July 2016) - Tsuchiya, Taketsugu; Takamura, Takaaki; Soga, Yoshimitsu; Iida, Osamu; Hirano, Keisuke; Suzuki, Kenji; Yamaoka, Terutoshi; Miyashita, Yusuke; Kitayama, Michihiko; Kajinami, Koji
Objective: Nitinol stenting could bring the better outcome in endovascular therapy for femoropopliteal disease. However, it might be expected that recent marked advances in both device technology and operator technique had led to improved efficacy of balloon angioplasty even in this segment. The aims of this study were to evaluate the clinical impact of balloon angioplasty for femoropopliteal disease and make risk stratification clear by propensity score matching analysis. Methods: Based on the multicenter retrospective data, 2758 patients (balloon angioplasty: 729 patients and nitinol stenting: 2029 patients), those who underwent endovascular therapy for femoropopliteal disease, were analyzed. Results: The propensity score matching procedure extracted a total of 572 cases per group, and the primary patency rate of balloon angioplasty and nitinol stenting groups after matching was significantly the same (77.2% vs 82.7% at 1 year; 62.2% vs 64.3% at 3 years; 47.8% vs 54.3% at 5 years). In multivariate Cox hazard regression analysis, significant predictors for primary patency were diabetes mellitus, regular dialysis, cilostazol use, chronic total occlusion, and intra-vascular ultra-sonography use. The strategy of balloon angioplasty was not evaluated as a significant predictor for the primary patency. After risk stratification using five items ( d iabetes mellitus, regular d ialysis, no use of i ntra-vascular ultra-sonography, c hronic total occlusion, and no use of c ilostazol: the DDICC score), the estimated primary patency rates of each group (low, DDICC score 0–2; moderate, DDICC score 3; high risk, DDICC score 4–5) were 88.6%, 78.3%, and 63.5% at 1 year; 75.2%, 60.7%, and 39.8% at 3 years; and 66.0%, 47.1%, and 26.3% at 5 years (p < 0.0001). The primary patency rate of balloon angioplasty and nitinol stenting groups was significantly the same in each risk stratification. Conclusion: This study suggests that balloon angioplasty does not have inferiority to nitinol stenting but does have favorable efficacy in femoropopliteal segment by careful risk stratification with the recent advance of technique.